Müllerian Remnant Cyst as a Cause of Acute Abdomen in a Female Patient with Müllerian Agenesis: Radiologic and Pathologic Findings - Mujtaba Mohammed; Mary Allen-Proctor; Andrij Wojtowycz (Case Reports in Radiology)
We report a case of a 17-year-old female with Müllerian agenesis who presented with right sided abdominal pain clinically suspicious for acute appendicitis. Multimodality imaging workup revealed a heterogeneous cystic right upper quadrant mass with surrounding fluid and inflammatory changes. Surgical resection of this mass was performed and a histopathologic diagnosis of a hemorrhagic Müllerian remnant cyst was made, which to the best of our knowledge has never been described in a patient with Müllerian agenesis.